2018
DOI: 10.1007/s00246-018-1952-2
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Cerebral Oxygenation Metabolism in Neonates with Hypoplastic Left Heart Syndrome or Transposition of the Great Arteries

Abstract: Optimizing oxygen delivery to the brain is one of the main goals in children with congenital heart defects after surgery. It has been shown that cerebral oxygen saturation (cSO2) is depressed within the first day after neonatal cardiopulmonary bypass surgery. However, peri-operative cerebral oxygen metabolism has not yet been assessed in previous studies. The aim of this study was to describe the peri-operative changes in cerebral oxygen metabolism in neonates with congenital heart defects following cardiopulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Unadjusted fractional tissue oxygen extraction values were significantly higher in CHD compared with control infants (p<0.02), indicating that CHD newborns either have increased cerebral metabolic rate or decreased oxygen delivery. Prior studies have reported higher fractional tissue oxygen extraction in term preoperative CHD infants compared with controls, who had fractional tissue oxygen extraction values comparable to our infants [27,[58][59][60]. We also found that higher fractional tissue oxygen extraction values were strongly associated with lower cerebral oxygen saturation levels when accounting for the effects of group and preductal peripheral arterial oxygen saturation on cerebral oxygen saturation values (p = <0.0001), consistent with findings from a study of CHD infants that fractional tissue oxygen extraction increased with declining venous oxygen content [61], a measure akin to NIRS-based cerebral oxygen saturation values.…”
Section: Cerebral Tissue Extractionsupporting
confidence: 83%
“…Unadjusted fractional tissue oxygen extraction values were significantly higher in CHD compared with control infants (p<0.02), indicating that CHD newborns either have increased cerebral metabolic rate or decreased oxygen delivery. Prior studies have reported higher fractional tissue oxygen extraction in term preoperative CHD infants compared with controls, who had fractional tissue oxygen extraction values comparable to our infants [27,[58][59][60]. We also found that higher fractional tissue oxygen extraction values were strongly associated with lower cerebral oxygen saturation levels when accounting for the effects of group and preductal peripheral arterial oxygen saturation on cerebral oxygen saturation values (p = <0.0001), consistent with findings from a study of CHD infants that fractional tissue oxygen extraction increased with declining venous oxygen content [61], a measure akin to NIRS-based cerebral oxygen saturation values.…”
Section: Cerebral Tissue Extractionsupporting
confidence: 83%
“…Therefore, we did not observe at which point cerebral oxygenation metabolism may fully recover in neonates and infants with intraoperative cerebral deoxygenations. However, studies in pediatric cardiac surgery showed that raised cFTOE and CMRO 2 after surgery normalized after 24-48 h. 12,21 Another limitation is that the patients' diagnoses, and therefore their operations, varied widely. Also, age and weight differed between the groups although not significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The probe transmits white light (500–800 nm, 1 nm resolution, <30 mW) into the tissue and recollects the reflected light. Based on the analysis of the spectral components of the reflected light in comparison with prerecorded deoxygenated and oxygenated hemoglobin, the device calculates oxygen saturation representing regional cerebral oxygen saturation (rcSO 2 ) (%) 12 . The continuous wave laser Doppler of the device (wavelength 830 nm, <30 mW) allows calculation of microperfusion (rcFlow, arbitrary units [AU]) based on Doppler shift of laser light, which correlates with blood flow velocitiy and the number of moving erythrocytes in the tissue 6,7 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Patients with complex CHD are at risk of cerebral hypoxemia before surgery. 6,[28][29][30][31][32] Due to hemodynamic alterations of cerebral blood flow, fetuses with complex CHD might develop brain injury even before birth. Brain development often is delayed and may itself result in greater vulnerability to cerebral white matter injury.…”
Section: Discussionmentioning
confidence: 99%